Development of glycated peptide enzyme sensor based flow injection analysis system for haemoglobin A1c monitoring using quasi-direct electron transfer type engineered fructosyl peptide oxidase - Hatada, Mika; Saito, Satomi; Yonehara, Satoshi; Tsugawa, Wakako; Asano, Ryutaro; Ikebukuro, Kazunori; Sode, Koji (Biosensors & bioelectronics, 2021)
Haemoglobin A1c (hemoglobin A1c, HbA1c) is an important long-term glycemic control marker for diabetes. The aim of this study was to develop an enzyme flow injection analysis (FIA) system using engineered fructosyl peptide oxidase (FPOx) based on 2.5th generation principle for an HbA1c automated analytical system. FPOx from Phaeosphaeria nodorum (PnFPOx) was engineered by introducing a Lys residue at the R414 position, to be modified with amine reactive phenazine ethosulfate (arPES) in proximity of FAD. The engineered PnFPOx mutant with minimized oxidase activity, N56A/R414K, showed quasi-direct electron transfer (quasi-DET) ability after PES-modification. The FIA system was constructed by employing a PES-modified PnFPOx N56A/R414K and operated at 0 V against Ag/AgCl. The system showed reproducible responses with a linear range of 20–500 μM for both fructosyl valine (FV) and fructosyl valylhistidine (FVH), with sensitivities of 0.49 nA μM−1 and 0.13 nA μM−1, and the detection limits of 1.3 μM and 2.0 μM for FV and FVH, respectively. These results indicate that the enzyme electrochemical FIA system covers the clinical range of HbA1c detection for more 200 consecutive measurements. Protease digested three different levels of HbA1c samples including healthy and diabetic range subjects were also measured with the FIA system. Thus, it will be possible to develop an integrated system consisting of sample pretreatment and sample electrochemical measurement based on an FIA system possessing quasi-DET type PnFPOx. •The enzyme FIA system using engineered PnFPOx based on 2.5th generation principle was developed.•PnFPOx was engineered by introducing Lys (R414K) to be modified with arPES at the proximity of FAD.•FIA system showed the linear range of 20–500 μM for both fructosyl valine and fructosyl valylhistidine.•Developed FIA system showed the ability of more than 200 times consecutive measurement.•Protease digested HbA1c samples with three different HbA1c levels were measured with developed FIA system.